2008
DOI: 10.1111/j.1365-2621.2006.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trehalose on the glass transition and ice crystal growth in ice cream

Abstract: SummaryThe effects of trehalose and sucrose on the rate of ice crystal growth in ice cream during accelerated shelf-life were compared. Experimental and theoretical freezing curves were shown to be in good agreement. Glass transition temperatures (T g ) of maximally freeze concentrated trehalose and sucrose solutions (40% w ⁄ w) were found to be )39.5°C and )47°C respectively. For ice cream mixes, the T g value increased from )46.4°C for the 100% sucrose-based mix to )42.0°C for the 100% trehalose sweetened ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
2
23
0
10
Order By: Relevance
“…For trehalose, this result may be explained by two phenomena. Firstly, freeze concentrated solutions of this sweetener have been reported to show glass transition temperatures (Tg) between −22°C and −46°C (Whelan et al, 2008a), near to the range of temperatures reached in our study during ice cream hardening and conditioning (−30°C and −16°C). Thus, it can be argued that during processing the formation of an amorphous phase occurs, revealing a solid-like behavior in the final matrix.…”
Section: Ice Cream MIX Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…For trehalose, this result may be explained by two phenomena. Firstly, freeze concentrated solutions of this sweetener have been reported to show glass transition temperatures (Tg) between −22°C and −46°C (Whelan et al, 2008a), near to the range of temperatures reached in our study during ice cream hardening and conditioning (−30°C and −16°C). Thus, it can be argued that during processing the formation of an amorphous phase occurs, revealing a solid-like behavior in the final matrix.…”
Section: Ice Cream MIX Propertiessupporting
confidence: 82%
“…Trehalose-containing samples showed a significantly (p < 0.05) lower extrusion temperature than the reference, suggesting a lower ability of this sweetener to decrease the freezing point in comparison with sucrose. Actually, trehalose showed a relative FPD of 0.90 ± 0.01, significantly (p < 0.05) lower than those of sucrose, as already reported by Whelan et al (2008a). A particular and unexpected behavior was observed for the ice cream containing erythritol (E100) that reached the consistency required for the extrusion at a higher temperature and with a longer freezing process (higher extrusion time) than sucrose.…”
Section: Ice Cream MIX Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…It is also interesting the fact that trehalose and in lesser extent maltose, did lead to the increase of T g despite they have similar molecular weight to that of sucrose. Whelan et al (2008) have demonstrated that the addition of trehalose in ice cream systems may lead to significant elevation of glass transition temperature without having a clear impact on nucleation -ice crystallization phenomena.…”
Section: Effects Of Bulk Sweeteners On Instrumental Propertiesmentioning
confidence: 98%
“…1 The ice crystal size distribution in frozen salmon subjected to temperature modulation was characterized by X 50 , the slope of the cumulative distribution at X 50, and the percentage ice crystal growth rate. 17 The percentage ice crystal growth rate and the slope were determined with Eqs. 1 and 2, respectively.…”
Section: Glassy Statementioning
confidence: 99%